Kırka Bor İşletmesi Atık Göletlerindeki Sulardan Borun Kazanılması - Kökkılıç, Ozan (Fen Bilimleri Enstitüsü, 2015)
Kırka Bor İşletmesi Atık Göletleri’ndeki sulardan borun kazanılması isimli tez çalışması kapsamında, Kırka atık göletlerinden alınan su üzerinde boru kazanmak için, kimyasal çöktürme deneyleri yapılmıştır. Kırka Bor İşletmesi atık göletlerde yaklaşık 6.500.000 m3 su bulunmaktadır. Atık suların 3,9 g/L bor içerdiği saptanmıştır. Öncelikle, sıvıda yüksek konsantrasyonlarda olan borun kimyasal çöktürme yöntemleriyle kazanılmasına çalışılmıştır. Yapılan kimyasal çöktürme deneylerinde çöktürücü reaktif olarak Ca(OH)2 ve MgO kullanılmıştır. Çöktürme deneyleri iki aşamada gerçekleştirilmiştir. Birinci aşamada çöktürücü olarak Ca(OH)2, MgO ve Ca(OH)2+MgO reaktifleri miktarı, başlangıç pH’sı, karıştırma süresi, çökme ve dinlenme süresi gibi etkenlerin boru çöktürmeye etkisi incelenmiştir. İlk aşama kazanma deneylerinde elde edilen optimum sonuç; 20 kg/m3 Ca(OH)2 ilavesi ile 22±2 0C çözelti sıcaklığı, başlangıç pH’sı 6, 4 saat çökme süresinde bor kazanma verimi % 87, çözeltide kalan bor miktarı da 0,51 g/L olarak bulunmuştur. İkinci aşama deneylerde çöktürücü olarak Ca(OH)2, pH düzenleyici ve ortamdaki Ca++ iyonlarını giderici olarak Al2(SO4)3·18H2O kullanılmıştır. Deneylerde Ca(OH)2 ve Al2(SO4)3·18H2O’ın çökmeye etkisi incelenmiştir. İkinci aşama deneylerinde elde edilen optimum sonuç; 60 kg/m3 Al2(SO4)3·18H2O ilavesine 20 kg/m3 Ca(OH)2 ilavesi ile 22±2 0C çözelti sıcaklığında, bor çöktürme verimi % 74,5, toplam bor çöktürme verimi %96,7 ve çözeltide kalan bor miktarı da 0,13 g/L olarak bulunmuştur.

In the scope of this Msc. project “Beneficiation of the Boron from Waste Water of Kırka Tailing Ponds”, experiments have been conducted for recovery boron by precipitation from the effluents of Kırka Borax Concentrator. Tailing Ponds of Kırka Borax Concentrator hold nearly 6.500.000 m3 water with a boron concentration of 3,9 g/L. In the first stage of the research, chemical precipitation methods have been used to recover boron, as its concentration level is very high. In the chemical precipitation experiments, Ca(OH)2 and MgO was used as precipitant reactants. Precipitation experiments were made in two steps. In the first step; factors like quantity of the precipitant reagent such as Ca(OH)2, MgO and Ca(OH)2+MgO, starting pH value, agitation time, and precipitation time and were studied in order to understand their effects on precipitation mechanism of boron. The optimum conditions found after the first step of beneficiation experiments were; 20 kg/m3 of Ca(OH)2 addition, 22±2 0C solution temperature, starting pH of 6 and a precipitation time of 4 hours. As a result of test conducted under optimum conditions 87% of boron was precipitated and the boron concentration in the solution was reduced to 0.51 g/L. In the second stage of the investigation was, Ca(OH)2 used as precipitant reagent and Al2(SO4)3·18H2O was used as pH regulator. The optimum conditions found after the second step of beneficiation experiments were; 20 kg/m3 of Ca(OH)2 and 60 kg/m3 Al2(SO4)3·18H2O addition, 22±2 0C solution temperature and a precipitation time of one hours. As a result of test conducted under optimum conditions 74,5% of boron was precipitated and the boron concentration in the solution was reduced to 0.13 g/L. According to the overall precipitation test results, the total boron precipitation was found almost 96,7%.
Beneficiation Of The Boron From Waste Water Of Kirka Tailing Ponds
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2003
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2003
Keywords: bor; bor kazanma; kimyasal çöktürme; boron; boron recovery; chemical precipitation